EXAMINING THE INFLUENCE OF TEACHER’S EMOTIONAL INTELLIGENCE ON JOB SATISFACTION: A STUDY OF SECONDARY SCHOOL TEACHERS IN MUZAFFARABAD - Mughal, Inaam ul Haq; Zia, Dr. Asma; Khurshid, Dr. Rabia (JELM, 2025)
This study investigates the influence of teacher emotional intelligence on job satisfaction among secondary school educators in Muzaffarabad. Emotional intelligence, a crucial aspect of effective teaching, has gained increasing attention for its potential influence on job satisfaction and overall professional performance. Utilizing a quantitative research method, data was collected from a 254 sample of secondary school teachers through structured questionnaires the survey instrument was adopted after written permission included standardized measures to assess teacher emotional intelligence (Schutte, Malouff, & Bhullar, (2009) Emotional Intelligence Scale and job satisfaction (Paul. Spector, (1994) Job Satisfaction Survey) to measure emotional intelligence and job satisfaction levels. Statistical analyses, including correlation and regression techniques, were employed to explore the relationships between emotional intelligence dimensions and job satisfaction. The study findings reveal significant correlations between emotional intelligence and job satisfaction levels among secondary school teachers. In addition, regression analyses specify that emotional intelligence dimensions significantly predict job satisfaction among educators. The implications of these results emphasize the significance of development emotional intelligence skills in teacher training programs to increase job satisfaction and eventually improve the quality of education in Muzaffarabad's secondary schools.